Array of disordered silicon nanowires coated by a gold film for combined NIR photothermal treatment of cancer cells and Raman monitoring of the process evolution. (10th August 2018) - Convertino, Annalisa; Mussi, Valentina; Maiolo, Luca; Ledda, Mario; Lolli, Maria Grazia; Bovino, Fabio Antonio; Fortunato, Guglielmo; Rocchia, Massimiliano; Lisi, Antonella
Abstract: Photothermal therapy (PTT) assisted by nanomaterials is a promising minimally invasive technique for cancer treatment. Here, we explore the PTT properties of a silicon- and gold-based nanostructured platform suitable for being directly integrated in fibre laser systems rather than injected into the human body, which occurs for the most commonly unreported PTT nanoagents. In particular, the photothermal properties of an array of disordered silicon nanowires coated by a thin gold film (Au/SiNWs) were tested on a monolayer of human colon adenocarcinoma cells (Caco-2) irradiated with a 785 nm laser. Au/SiNWs allowed an efficient photothermal action and simultaneous monitoring of the process evolution through the Raman signal coming from the irradiated cellular zone. Strong near infra-red (NIR) absorption, overlapping three biological windows, cell-friendly properties and effective fabrication technology make Au/SiNWs suitable both to be integrated in surgical laser tools and as an in vitro platform to develop novel PTT protocols using different cancer types and NIR sources.